Immobilization and stabilization of papain on chelating sepharose: a metal chelate regenerable carrier - Afaq, Sarah; Iqbal, Jawaid (Electronic Journal of Biotechnology, 2001)
A method for immobilization of papain has been selected based on the interaction between its histidine, cysteine and tryptophan residues with the immobilized metal ion (IMI) carrier for maximum binding on a small volume of the carrier. The immobilized papain retained high activity has improved thermal stability and the carrier could be recovered from the spent bound enzyme, to be reused. Reimmobilization of papain on the regenerated matrix was equally effective with the retention of maximum enzyme activity.